2008
DOI: 10.1186/1472-6750-8-27
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of soybean protein P34 from oil bodies using hydrophobic interaction chromatography

Abstract: Background: Soybeans play a prominent role in allergologic research due to the high incidence of allergic reactions. For detailed studies on specific proteins it is necessary to have access to a large amount of pure substance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
(24 reference statements)
0
13
0
2
Order By: Relevance
“…In previous studies, P34 was extracted from soybean oil bodies using hydrophobic interaction chromatography (Sewekow et al 2008). A subsequent purification, however, is in any case necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, P34 was extracted from soybean oil bodies using hydrophobic interaction chromatography (Sewekow et al 2008). A subsequent purification, however, is in any case necessary.…”
Section: Discussionmentioning
confidence: 99%
“…IgE binding assays using immunoglobulin from soybean-sensitive individuals indicated that 65 % of the total allergenic response was induced by P34 (Helm et al by disulfide linkages in the 7S globulin fraction and may play a role in protein folding (Helm et al 2000). As a thiol protease, P34 is a member of the papain superfamily (Sewekow et al 2008) and has a tendency to bind to lipid and oil, which is likely significant in its role as an allergen (Mills et al 2004). P34 exhibits post-translational production derived from a 46-to 47-kDa precursor protein by the partial removal of 122 Nterminal amino acid residues, and its tertiary conformation was similar to the papain family .…”
Section: Introductionmentioning
confidence: 96%
“…For the latter, the 15S fraction corresponds to 1% of the globulins, has a high molecular mass (700 kDa) and has an isoelectric point of 4.5. Furthermore, the known proteins in soybean seeds with high allergenic potential are mainly composed of a 34-kDa maturing seed protein (also known as P34, Gly m Bd 30 K or Gly m 1) (Sewekow et al, 2008), the 23-kDa protein Gly m Bd 28 K (Xiang et al, 2004), β-conglycinin (Krishnan et al, 2009), the glycinin Gly m 6 (Holzhauser et al, 2009), lectin andlypoxygenase (L'Hocine andBoye, 2007), and a Kunitztype protease inhibitor (Roychaudhuri et al, 2004). There are also some allergenic proteins in seed shell, such as Gly m 1.0101, Gly m 1.0102, Gly m 2, Gly m 3, and SAM 22 (Gly m 4).…”
Section: Purification and Characterization Approachesmentioning
confidence: 99%
“…Trata-se de uma protease que pertence à superfamília papaína. Nas células vegetais, apresenta-se associada a frações lipídicas e localiza-se no interior de vacúolos de proteínas de armazenamento (SEWEKOW et al, 2008;KALINSKI et al, 1992). Muitas proteases tióis estão associadas à germinação, ou seja, na degradação protéica e mobilização de proteínas para o desenvolvimento da planta.…”
Section: Identificação Das Proteínas Por Espectrometria De Massasunclassified
“…A P34 é reportada como uma dos principais alérgenos da soja em seres humanos sensíveis e corresponde a cerca de 2-3% das proteínas da soja (HERMAN et al, 2003, SEWEKOW et al, 2008. Apresenta peso molecular de 28,643 Da e na forma glicosilada, a massa é ligeiramente maior, apresentando uma banda de 32kDa em géis SDS-PAGE (SEWEKOW et al, 2008).…”
Section: Identificação Das Proteínas Por Espectrometria De Massasunclassified